Polish Complementary Schools in Ireland: Language, Heritage, Capital - Pedrak, Agnieszka Kamila (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2024)
In recent decades, multiple cultures and languages have significantly enriched Irish society and classrooms due to increased inward migration. Many migrant families aim to maintain and transmit their linguistic and cultural heritage to the young generations, who also learn English and Irish in their mainstream primary and post-primary school settings. Some of them also participate in complementary schooling that offers heritage language (HL) education outside the regular school hours. This research project provides a comprehensive perspective as it investigates the influence of Polish complementary schooling in Ireland on maintaining the Polish language and identity (re)negotiation among Polish migrant children, parents, and teachers in Ireland. The study employs a mixed-methods design, combining quantitative methods, such as an online questionnaire, with qualitative methods, including semi-structured interviews and language portraits. Through the theoretical lens of Cultural Capital, Family Language Policy, and Investment in Language Learning, this research aims to understand the reasons behind Polish migrants’ participation in HL schools. In light of their views on ‘home’ and belonging, as well as their language beliefs and practices in different contexts, it also looks into the advantages and challenges that they associate with Polish complementary schooling. Additionally, this study investigates the operational aspects of Polish schools in Ireland and the implications of the Covid-19 pandemic on learning and teaching in these settings in 2020-2021. The findings are placed within the wider framework of societal bilingualism and foreign language education in Ireland and globally and offer valuable contributions to understanding the role of complementary schooling on HLs learning and teaching at individual, family, school, and societal levels. Therefore, this research project brings important insights into the ongoing debate surrounding the (mis)recognition of HL bilingualism/multilingualism and complementary schooling in national language education policies and practices in Ireland and worldwide.
Polish as a Heritage Language in Ireland
APPROVED
Keywords: Complementary Schools; Heritage Language Education; Linguistic and cultural diversity; Migrant Parents; Migrant Teachers; Bilingual Children; Ireland